2009
DOI: 10.1016/j.devcel.2009.06.015
|View full text |Cite
|
Sign up to set email alerts
|

Arabidopsis DOF Transcription Factors Act Redundantly to Reduce CONSTANS Expression and Are Essential for a Photoperiodic Flowering Response

Abstract: Flowering of Arabidopsis is induced by long summer days (LDs). The transcriptional regulator CONSTANS (CO) promotes flowering, and its transcription is increased under LDs. We systematically misexpressed transcription factors in companion cells and identified several DOF proteins that delay flowering by repressing CO transcription. Combining mutations in four of these, including CYCLING DOF FACTOR 2 (CDF2), caused photoperiod-insensitive early flowering by increasing CO mRNA levels. CO transcription is promote… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

17
589
0
2

Year Published

2012
2012
2023
2023

Publication Types

Select...
6
3

Relationship

0
9

Authors

Journals

citations
Cited by 523 publications
(608 citation statements)
references
References 56 publications
17
589
0
2
Order By: Relevance
“…Genetic analyses have confirmed that several AtCDFs of Arabidopsis function redundantly to suppress CO activity, inhibit FT transcription, and repress the floral transition (Fornara et al, 2009). These CDFs, in turn, are removed by the GI/FKF1/CDF complex that targets the CDFs for degradation.…”
Section: Atcdf1 Functions In the Leaf As A Regulator Of Floweringmentioning
confidence: 99%
“…Genetic analyses have confirmed that several AtCDFs of Arabidopsis function redundantly to suppress CO activity, inhibit FT transcription, and repress the floral transition (Fornara et al, 2009). These CDFs, in turn, are removed by the GI/FKF1/CDF complex that targets the CDFs for degradation.…”
Section: Atcdf1 Functions In the Leaf As A Regulator Of Floweringmentioning
confidence: 99%
“…For example, the transcriptional expression of FT is positively regulated by CONSTANS (CO), which encodes a putative zinc finger transcription factor (TF) (Putterill et al, 1995). Under favorable conditions, light signaling and the circadian clock coordinately control the activity of CO, which directly regulates the transcription of FT to promote flowering (Suárez-López et al, 2001;An et al, 2004;Imaizumi et al, 2005;Sawa et al, 2007;Fornara et al, 2009). On the other hand, the expression of FT is also negatively regulated by several transcriptional repressors, such as FLOWERING LOCUS C (Helliwell et al, 2006;Searle et al, 2006), SHORT VEGETATIVE PHASE (Lee et al, 2007), TEMPRANILLO1 (Castillejo and Pelaz, 2008), and SCHLAFMŰTZE (SMZ) (Mathieu et al, 2009).…”
Section: Introductionmentioning
confidence: 99%
“…The highest similarity of Pn FKF1 is to Arabidopsis FKF1 rather than to other FKF1-related proteins including the Arabidopsis paralogs such as ZEITLUPE (ZTL) and LKP2, which are mainly involved in the control of clock functions in this plant. 16,2628 The deduced amino acid sequence of the protein encoded by PnCDF2 was also most similar to those of Arabidopsis CDFs and related proteins, that also contain the conserved DOF DNA-binding domain in their deduced amino acid sequence 14,29 (Supplementary fig. 3).…”
mentioning
confidence: 78%
“…14,29 Also, expression of both of these genes began to rise constantly from transfer to LL regardless of when plants were shifted to DD (Figure 1C, F, I, L, Supplementary Figure 1E, F, G, H). This indicates that despite dusk-set circadian expression of Pn FT , circadian expression of PnFKF1 and PnCDF2 is not affected by light-to-dark transitions.…”
mentioning
confidence: 94%